THE INFLUENCE OF BRAND IMAGE, PERCEIVED QUALITY AND COUNTRY OF ORIGIN TOWARD CONSUMER PURCHASE DECISION OF SMARTPHONE PRODUCT IN MANADO - Nelwan, Julia (Jurnal Berkala Ilmiah Efisiensi, 2016)
Smartphone is one of communication tools that often used by people around the world. People buy a smartphone not only because of their needs, but also consider about another aspect of the smartphone. When consumer selecting the smartphone, they also consider about the brand image, perceive quality and the country of origin of the smartphone. This study aims to understand the influence of brand image, perceived quality and country of origin toward consumer purchase decision of smartphone in Manado. 100 customers were surveyed as samples. Multiple regression analysis was used to test the relationship among variables. The result indicated that brand image, perceived quality and country of origin simultaneously and significantly influence the consumer purchase decision of smartphone product in Manado. The characteristic of brand image and perceived quality has a significant effect on consumer purchase decision while country of origin has no significant effect on consumer purchase decision.